1994
DOI: 10.1103/physrevd.50.6824
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of data on soft photon production in hadronic interactions

Abstract: The glob model of Lichard and Van Hove and the modified soft annihilation model (MSAM) of Lichard and Thompson are used as a phenomenological tool for relating results from various experiments on soft photon production in high energy collisions. The total phenomenological expectation is composed of contributions from classical bremsstrahlung, the soft annihilation model and the glob model. The empirical excess above the background from hadronic decays at very small longitudinal momenta of photons is well repro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Many different models have been presented to describe the anomalous soft photons as arising from quantized bosons [34][35][36] or from a continuous spectrum [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. We shall focus our attention on the quantized boson description of [34][35][36] which has the prospect of linking the anomalous soft photons with the X17 and E38 particles.…”
Section: Jhep08(2020)165mentioning
confidence: 99%
“…Many different models have been presented to describe the anomalous soft photons as arising from quantized bosons [34][35][36] or from a continuous spectrum [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. We shall focus our attention on the quantized boson description of [34][35][36] which has the prospect of linking the anomalous soft photons with the X17 and E38 particles.…”
Section: Jhep08(2020)165mentioning
confidence: 99%
“…The latter was expected to be the main source of the direct soft photons in kinematic ranges under study (see [8][9][10]), while the observed signals were found in [1][2][3][4][5][6][7] to be several times higher than the bremsstrahlung predictions. No theoretical explanation of this excess is available so far; reviews of the theoretical approaches to the problem can be found in [11,12] (see also the references in [1]).…”
Section: Introductionmentioning
confidence: 99%
“…In several models aiming at an explanation of the anomalous soft photon effect, the possi- bility of interference is discarded or ignored altogether. In the Van Hove and Lichard model of the cold quark-gluon plasma as the source of the soft photons [18,56,57], the photon rate is proportional to the (incoherent) sum of cross sections of the photon production in head-on collisions of partons, mainly in the processes of annihilation (qq → gγ ) and Compton scattering (qg → qγ ) (note however a critical remark to this approach with a reference to the LPM effect given in the paper [58]). Also the model [59], based on the Unruh−Davies effect (a purely quantum-mechanical phe- nomenon which promotes zero-point electromagnetic field fluctuations to the level of real quanta [60] and leads to the thermal radiation from charged particles undergoing acceleration in addition to the bremsstrahlung), assumes an incoherent sum of the radiation intensities from different quarks.…”
Section: General Remarksmentioning
confidence: 99%
“…1 Known for more than 20 years, they however still lack a theoretical explanation, in spite of being under active investigation. Reviews of the theoretical approaches to the problem can be found in [17,18] (see also Refs. in [1]).…”
Section: Introductionmentioning
confidence: 99%